Unwritten Agreement Between the Disposer and the Debtor (Case Study at Boyolali Market) - Muhammad Yusril Januar; K Kuswardani (Proceeding International Conference Restructuring and Transforming Law, 2023)
The presence of a plecit bank at the Boyolali Traditional Market can provide a solution for traders who need funds. unreasonable/inappropriate, the collection system tends to be rough which of course is not in accordance with the operational standards of Bank Indonesia and/or the Financial Services Authority (OJK). So that this journal will analyze the position of plecit banks and regarding the legal force of unwritten agreements according to Indonesian civil law. Research is used with empirical juridical methods where data is obtained based on research in the field by conducting interviews and observations.